(untitled) (Global Journal of Human-Social Science, 2013)
This paper attempts to look at the Niger Delta Crisis from a socio-politico-ecological perspective. By way of deductive reasoning premised on the theory of existentialism, the paper observes that the restiveness, violence as well as criminality of the people of the Niger Delta represent their desperate struggle for self-preservation and ’selfdetermination’ in an environment that is indifferent and hostile to their sustainable livelihood and survival. The paper thus submits quite pessimistically that the Niger Delta crisis will prevail, until and unless the organic context which precipitates it (characterized by ecocide, state predation, corporate buccaneerism, environmental and human rights abuse, socioeconomic and political marginalization, economic expl:oitation etc.) is comprehensively and adequately transformed.